2022
DOI: 10.1128/jvi.00957-22
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Macrophage-Tropic HIV-1 Infection of Central Nervous System Cells and the Influence of Inflammation

Abstract: The major feature of HIV-1 pathogenesis is the induction of an immunodeficient state in the face of an enhanced state of inflammation. However, for many of those infected, there can be an impact on the central nervous system (CNS) resulting in a wide range of neurocognitive defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…HAD is typically a multinucleated-cell encephalitis [129131] involving myeloid cell infection with M-tropic viruses [132134] developing in untreated individuals with advanced systemic infection [32, 33, 37], while NSE is generally a T-cell mediated disease with notable CD8+ T cell infiltration pathologically [102] and T-tropic HIV-1 infection (Kincer et al, unpublished observation). NSE usually occurs in the setting of limited CNS penetration of one or more antiretroviral drugs along with resistance to other drugs [9496, 101, 103, 104, 135].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HAD is typically a multinucleated-cell encephalitis [129131] involving myeloid cell infection with M-tropic viruses [132134] developing in untreated individuals with advanced systemic infection [32, 33, 37], while NSE is generally a T-cell mediated disease with notable CD8+ T cell infiltration pathologically [102] and T-tropic HIV-1 infection (Kincer et al, unpublished observation). NSE usually occurs in the setting of limited CNS penetration of one or more antiretroviral drugs along with resistance to other drugs [9496, 101, 103, 104, 135].…”
Section: Resultsmentioning
confidence: 99%
“…was diagnosed in individuals taking ART with suppression of plasma HIV-1 RNA below pretreatment levels but with higher concentrations of HIV-1 RNA in CSF than plasma [94, 113, 135]. Three types of CSF escape were distinguished: NSE in which individuals presented clinically with new neurological symptoms and signs that were attributed to CNS HIV-1 infection and without alternative cause after diagnostic studies; asymptomatic escape ( AsE ) were neurologically asymptomatic individuals identified by CSF and blood HIV-1 RNA findings during participation in cohort studies; and secondary CSF escape ( 2ryE ) was diagnosed on the basis of CSF and plasma measurements in the context of another, non-HIV-1 nervous system infection [100].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have highlighted that interferon can inhibit HIV infection of primary microglia but less so of iPSC-derived microglia, as well as macrophages. 111 , 112 Interestingly, interferon may promote latency in macrophages. 113 An important feature of HIV infection of microglia identified in previous in vitro studies has been the rapid induction of viral latency.…”
Section: Discussionmentioning
confidence: 99%
“…Whether interferon induction inhibits or enhances HIV infection and latency in microglia remains to be understood. Recent studies have highlighted that interferon can inhibit HIV infection of primary microglia but less so of iPSC-derived microglia, as well as macrophages (Nasr et al 2017; Woodburn et al 2022). Interestingly, interferon may promote latency in macrophages (Dickey, Martins, Planelles, and Hanley 2022).…”
Section: Discussionmentioning
confidence: 99%